Diagnosis of the winemaking process in the Planalto Norte Catarinense (Research, Society and Development, 2022)
Although viticulture is an activity that has been carried out in the region of Planalto Norte Catarinense, it is in recent years that there has been a greater incentive and technological advances in vine cultivation and grape processing, and thus, information on the enological technologies used in winemaking. In this context, the objective is to characterize the winemaking process in the Planalto Norte Catarinense. The present work was carried out by the Federal Institute of Santa Catarina - Campus Canoinhas through qualitative research, within a descriptive perspective. The collection of information took place between the months of June and August 2019, through a questionnaire. Rural producers who cultivate the vine and make or intend to make wines participated in the present work. The elaboration of wines in the region of Planalto Norte Catarinense is a reality, however, there was a small number of producers who use oenological inputs and techniques and adequate care during the elaboration processes that aim to obtain a quality wine. This may be directly related to the low number of producers who at no time had a course, qualification, or training on winemaking. Therefore, it is necessary actions that aim to empower producers, guiding them on techniques and care to be adopted during the elaboration process, as well as the importance of using oenological inputs to obtain high quality wines.